Forms of Hatred : The Troubled Imagination in Modern Philosophy and Literature - Donskis, Leonidas (Leiden ; Boston : BRILL, 2003)
This book analyzes such symbolic designs of the modern troubled imagination as the conspiracy theory of society, deterministic concepts of identity and order, antisemitic obsessions, self-hatred, and the myth of the loss of roots. It offers, among other things, the unique East-Central European materials incorporated in a broad, imaginative synthesis and critique of contemporary social analysis.
Foreword by Timo Airaksinen -- Preface -- Acknowledgments -- Introduction -- PART 1 The Making and Unmaking of Enemies: Evil and the Troubled Imagination -- ONE The Conspiracy Theory of Society: From Sir John Mandeville to the Modern Troubled Imagination -- TWO Transferred Loyalties, Fabricated Identities, and Organized Hatred: The Politics of True Believers vs. the Literature of Skeptics -- PART 2 The Uncertainties of Modernity: Ambivalence and the Troubled Identity -- THREE Alternative Modernity? Marxism, Modern Ideocracy, and the Secular Church -- FOUR Modernity and the Loss of Roots, or Two Modes of Being of the Troubled Identity -- Notes -- Bibliography -- About the Author -- Index.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Group identity; Hate -- Political aspects; Social conflict; Social Identification; Identité collective; Haine -- Aspect politique; group identity; Group identity; Hate -- Political aspects; Social conflict